Investigating Strategies and Ideology in Translating Middle East News Headlines from English to Arabic: A Critical Discourse Analysis - Al Hindi, Sara Mohammed; Altuwairesh, Nasrin Salama (Jordan Journal of Modern Languages & Literatures, 2025)
Ideological manipulation in news translation has always been a topic that demands attention. There seems to be a need for a focus on using translation strategies as a tool to promote ideology, which should complement research in translation studies. This study focuses on the topic of translation strategies and ideology by investigating how news headlines of the Middle East are reported in the American news networks and how they are translated by Arab news networks. The samples consist of news headlines, where the Source Texts (ST) are English news headlines and the Target Texts (TT) are the Arabic translation by Arab news networks on their official Twitter accounts. This study is a Critical Discourse Analysis (CDA) where the data is analyzed based on Chesterman’s (1997) pragmatic strategies model, and the analysis is associated with the ideological square of Van Dijk (1998). The results show that using certain translation strategies has led to some changes that enabled Arab news networks with the representation of positive Us and negative Them. The study concluded that translated news is more likely to have its own set of ideological standards imposed on it by the news organization reporting the news. Keywords: News translation, Translation strategies, Ideology, Middle East news, Social media.